Sistem Informasi Penjualan Makanan Menggunakan Metode User Centered Design Berbasis Web - Yuli Pratama Aldi; Mohammad Iwan Wahyuddin (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
One of the uses of the internet in processing an information can be applied to the design of a system. One of them is a sales site that makes it easier for entrepreneurs to promote their products and make it easier for people to find information and needs. The limitations of product marketing are an obstacle in increasing sales turnover and recording inventory as well as recording sales reports which are still done manually which will have a bad impact so that it hampers the sales process. The purpose of this study is to create an online store website using the User Centered Design method to provide better service for customers and provide convenience for sellers. Researchers use the waterfall method, this method is used to create a software system that is flowing starting from design analysis, coding, and testing. This program is tested using the Blackbox method by entering existing data. This design uses UML or the abbreviation of Unified Modeling Language, PHP language as script, and MySQL database.